Music Derived from Other Sources. - Barlow, Clarence (International Journal of the Humanities, 2012)
One imagines composed music as originating in the mind of an author. Indeed, I have for the last five decades been composing music in this fashion. However, for the last four decades I have also been repeatedly attracted to various methods of deriving music from sources both inside and outside the field. These sources have been linguistic, acoustic (field recordings), visual and mathematical (parametric formulae) as well as other works of music. For most of these operations I have resorted to strict algorithmic means and the use of computer programming. In this paper I will outline the sources mentioned above and go a little into detail in some of them. For instance the linguistic: I have used text orthography, spectral analyses of human speech, digital recordings of the human voice, and synthetic semantic structures. In the case of the visual, it was the conversion of pixellated photographs, city silhouettes, abstract films and geometric models as well as the visualization of algorithmically generated music that played a central role in the compositional plan. In other words, the paper will provide a general overview and examples. This is the first time I have covered more than one type of source in a single article.